2016
DOI: 10.1590/1983-084x/15_220
|View full text |Cite
|
Sign up to set email alerts
|

Changes in root morphology and dry matter production in Pfaffia glomerata (Spreng.) Pedersen accessions in response to excessive zinc

Abstract: Zinc (Zn) participates of numerous metabolic processes in plants. However, it can become toxic to plants in excessive concentrations in the soil. Pfaffia glomerata is a Brazilian medicinal species that has stood out because of its numerous chemical and functional properties, mainly by the triterpene saponins and ecdysteroids accumulated in its roots. This study aimed to evaluate the effects of zinc excess on many root morphological parameters of Pfaffia glomerata. A 4 x 3 factorial design was employed in a com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Results in the current study meet those reported by Stoláriková-Vaculíková et al (2015), who observed that high Zn levels did not reduce leaf dry weight production in Populus deltoides. Similarly, Bernardy et al (2016) reported that the BRA accession of Pfaffia glomerata (Spreng. ), grown in a hydroponic system presenting high Zn concentration, did not show reduced total and shoot dry weight production.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Results in the current study meet those reported by Stoláriková-Vaculíková et al (2015), who observed that high Zn levels did not reduce leaf dry weight production in Populus deltoides. Similarly, Bernardy et al (2016) reported that the BRA accession of Pfaffia glomerata (Spreng. ), grown in a hydroponic system presenting high Zn concentration, did not show reduced total and shoot dry weight production.…”
Section: Discussionmentioning
confidence: 90%
“…Zinc is an essential micronutrient for plants since it acts as a cofactor for several metalloproteins such as superoxide dismutase, carbonic anhydrase, dehydrogenases, proteases, peptidase, and phosphohydrolases (Brunetto et al, 2018;Somavilla et al, 2018). Despite the key role played by Zn in plant growth and development, this micronutrient can easily become toxic when its concentration reaches high levels in the soil and, consequently, in plant tissues (Bernardy et al, 2016).…”
Section: Toxicidade Do Zinco E Respostas Relacionadas à Tolerância Em...mentioning
confidence: 99%
See 1 more Smart Citation
“…The roots diameter increase is usually related to di culties of root growth, possible due to toxicity of one or more substances present in the medium where the plant is cultivated (Bernardy et al 2016). As can be observed in Fig.…”
Section: Root Morphologymentioning
confidence: 99%
“…This includes studies of root alterations caused by chemical excesses or deficiencies in maize, [31] in Medicago sativa L., [32] and the Brazilian medicinal plant Pfaffia glomerata. [33] In the latter case, the presence of zinc metal was the focus of study.…”
Section: Introductionmentioning
confidence: 99%